Efek Latihan Fisik Berkelanjutan Pada Pasien Pasca Mastektomi Radikal Modifikasi Terhadap Kejadian Limfedema dan Keterbatasan Gerak Sendi Bahu - Karla, Neidya; Prabowo, Tertianto; Biben, Vitriana (Majalah Kedokteran Indonesia, 2019)
Aim: Determine the effects of continual physical exercise on lymphedema and limitations of Range of Motion (ROM) of shoulder joint events in post-Modified Radical Mastectomy (MRM) patients. Methods: The Pretest-Posttest Control Group Design study with inclusion criteria are women aged d”60 years and BMI d”30 kg/m2 with a diagnosis of breast cancer post MRM. The control group received physical exercise during hospitalization and the treatment group received continual physical training until 16 weeks. This study using chi-square and Kolmogorov-Smirnov test for statistical analyzing.Results: Study was carried out on 24 subjects. There were no lymphedema and limitations of shoulder ROM in the group who receive continual physical exercise, but it is not statistically significant difference between groups (p greater than 0,05).Conclusion: This study shows that continual physical exercise could prevent the occurrence of lymphedema and limited ROM of shoulder joint in post MRM patients.